KEBIJAKAN PENGUSAHA YANG MENIMBULKAN KETIDAKADILAN GENDER TERHADAP BURUH PEREMPUAN DI PT DIDACHI TANGERANG - Nasihuddin, Abdul Aziz; Andriyan, Dody Nur; Indriasari, Dewi Chusna (Faculty of Law, Universitas Jenderal Soedirman, 2008)
The regulation of Industrial affair between women labour with company or entrepreneur, contain in Law Number 13 Year 2003 concerning Labour, and the regulation that protect women labour contain in Law Number 7 Year 1984 concerning Convention Of The Elimination Of All Forms Of Discrimation Against Women. But in the reality, there are many problems in the labour environment. Especially, if it concerning the unfairness of gender for the women, like the case in PT. DIDACHI, Tangerang. In this research, revealed about the entrepreneur policy that not only againts the regulation, but also in gender perspective they do the unfairness of gender in the term of behavior and policy. The labeling and the wrong interpretation about gender cause many policy that make the unfairness condition for the women labour in PT. DIDACHI, Tangerang. Kata kunci: Gender, interpretation of gender, unfairness of gender, women labour, entrepreneur, company.